TRANSFORMASI DIGITAL KOMUNITAS KESENIAN BARONGAN BERBASIS COMMUNITY-DRIVEN DEVELOPMENT UNTUK KEBERLANJUTAN BUDAYA LOKAL DI KELURAHAN KARANGSARI, KENDAL - Triyono Triyono; Julieta Putri Nirmala Wibowo; Naintina Lisnawati; Ahmad Fauzi Wahyuddin; Putri Karina D’amor; Hafiz Rama Devara; Mastur Mastur (Universitas Mataram, 2026)
Traditional arts are an important part of cultural heritage that needs to be preserved amid the tide of globalization. One such art form is Barongan, which developed in Karangsari Urban Village, Kendal, through the New Putro Budoyo community. However, this community faces obstacles in promotion, documentation and publication, threatening the sustainability of the art form. This community service programme was implemented using a Community Driven Development (CDD) approach that emphasises active community participation. The main activities included the creation of profile videos, social media management training, and poster design training using Canva. The results of the activities showed an increase in the community's capacity to utilise digital media, the creation of professional social media accounts, and the use of promotional products at the Karangsari Expo event. This programme not only produced tangible products but also built community independence in promoting traditional arts. Thus, CDD-based empowerment has proven effective in supporting sustainable cultural preservation while strengthening local identity in the digital era.